Hubungan jarak kehamilan, umur, dan paritas ibu terhadap kejadian abortus di RSUD Panembahan Senopati Bantul - Fatem Hamama; Suherni Suherni; Asmar Yetty Zein (Jurnal Kesehatan Ibu dan Anak, 2012)
The maternal mortality rate in Indonesia is reaching up to 228 per 100,000 live births in 2007. One of the possibilities is caused by bleeding abortion, and it is ranged 10-15%. Abortion is one of the health problems which cause morbidity and mortality are high. Objectives to determine is there any correlation of interval interpregnancy, maternal age, and parity with the incidence of abortion in pregnant women in Panembahan Senopati Bantul District Hospital in 2010. The researcher used Obseruationalstudy, with a cross-sectional design. The research takes place in Panembahan Senopali Bantul District Hospital. The study population was all pregnant women in 2010. The researcher uses random sampling with 323 respondents- This Analysis will use logistic regression test Results: The proportion of the incidence of abortion in Panembahan Senopati Bantul District Hospital is about 5.4 %. The 323 samples of pregnancies women were known as the result of calculation of the independent variables which related as predictor variables toward the incident of abortion was parity OR=0,714 p-value = 0.0293 (pvalue< 0,05). Age and interval interpregnancy in this research study does not correlate with the incidence of abortion because it has 0.4873 p-values and the interval interpregnancy has 0.5624 p-values (p-value> 0.05).Age and distance variables in this research can be regarded as moderator variables that affect the variables of parity for abortion.